2008
DOI: 10.1186/bf03352796
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of gamma-ray line intensities from the lunar surface

Abstract: Assuming different abundances of the Apollo lunar soil samples and the average spectrum of galactic cosmic ray protons, energy spectra of neutrons and gamma rays and emission rates of gamma-ray lines from major elements have been estimated by using the reviewed Monte Carlo simulation library Geant4 and nuclear data. Previously, such libraries were not able to reproduce gamma-ray lines properly for the planetary application. Results clearly show that the emission rate of gamma rays heavily depends not only on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Therefore, in this study, the γ ray dose from the natural radioactive isotopes was assumed to be the same as that on the Earth; it is 0.48 mSv/yr (United Nations Scientific Committee on the Effects of Atomic Radiation, 2000). The details of the dose calculation for neutron and γ ray are reported in Hayatsu et al (2007) and the further results from the simulation calculation for production and transportation of those secondaries is described in the paper (Yamashita et al, 2008). (Simpson, 1983) with the data from ACE/CRIS (Israel ., 2005).…”
Section: Leakage Neutrons and γ Raysmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in this study, the γ ray dose from the natural radioactive isotopes was assumed to be the same as that on the Earth; it is 0.48 mSv/yr (United Nations Scientific Committee on the Effects of Atomic Radiation, 2000). The details of the dose calculation for neutron and γ ray are reported in Hayatsu et al (2007) and the further results from the simulation calculation for production and transportation of those secondaries is described in the paper (Yamashita et al, 2008). (Simpson, 1983) with the data from ACE/CRIS (Israel ., 2005).…”
Section: Leakage Neutrons and γ Raysmentioning
confidence: 99%
“…(2-5) and with the parameters from Lal (1988) and McKinney et al (2006) as shown in Table 1, is isotropically irradiated to the central point on a surface of the cube. For the leakage fluxes of neutrons and γ rays, the difference between the GCR flux in this work and that in previous one shown in Table 1 is rather small in the estimate of dose on the lunar surface (Yamashita et al, 2008). The cube was made from average composition of soils found in Apollo 16 landing site (Heiken et al, 1991).…”
Section: Leakage Neutrons and γ Raysmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy and intensity of the lines identify the species of elements and their abundance in the lunar surface, respectively Reedy, 1978;Evans et al, 1993;Yamashita et al, 2008).…”
Section: Sources Of Lunar Gamma Raysmentioning
confidence: 99%
“…The fluences of GCR-produced neutrons and gamma rays on the lunar surface are calculated by using the Monte Carlo simulation library Geant4 release 8.0.p01 with the modified nuclear data library G4NDL3.9 12) and the hadronic interaction model called QGSP_BERT_HP. The lunar surface model is composed of materials with an averaged composition of soils brought back from the Apollo 16 landing site as the sample of highland and the Apollo 11 landing site as the sample of mare region.…”
Section: Secondary Components As Neutrons and Gammaraysmentioning
confidence: 99%